2009
DOI: 10.1111/j.1601-0825.2009.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐tooth extraction sepsis without locoregional infection – a population‐based study in Taiwan

Abstract: Tooth extraction is associated with a low but significant risk of postoperative sepsis, especially in the elderly and patients with underlying diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…Although this group of organisms are identified as an oropharyngeal commensal, their ability to produce thick pus and form abscesses are well documented 16–18 . S milleri abscess formations are known to occur at multiple body sites, with one report demonstrating that S milleri was the most common organism from the Streptococcus viridans group associated with abscess formation accounting for 71% of brain abscesses, 40% of abdominal abscesses and 34% of extra-abdominal abscesses 17–19. Disruption of the mucosal barrier, such as post tooth extraction, allows for invasion into underlying tissues and local spread as well as the potential for the organisms to spread haematogenously causing metastatic abscesses 17 19 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this group of organisms are identified as an oropharyngeal commensal, their ability to produce thick pus and form abscesses are well documented 16–18 . S milleri abscess formations are known to occur at multiple body sites, with one report demonstrating that S milleri was the most common organism from the Streptococcus viridans group associated with abscess formation accounting for 71% of brain abscesses, 40% of abdominal abscesses and 34% of extra-abdominal abscesses 17–19. Disruption of the mucosal barrier, such as post tooth extraction, allows for invasion into underlying tissues and local spread as well as the potential for the organisms to spread haematogenously causing metastatic abscesses 17 19 20.…”
Section: Discussionmentioning
confidence: 99%
“…S milleri abscess formations are known to occur at multiple body sites, with one report demonstrating that S milleri was the most common organism from the Streptococcus viridans group associated with abscess formation accounting for 71% of brain abscesses, 40% of abdominal abscesses and 34% of extra-abdominal abscesses 17–19. Disruption of the mucosal barrier, such as post tooth extraction, allows for invasion into underlying tissues and local spread as well as the potential for the organisms to spread haematogenously causing metastatic abscesses 17 19 20. Abscesses caused by S constellatus are more likely to be polymicrobial, with the co-isolates reflecting the site from which the specimen was obtained 20 21…”
Section: Discussionmentioning
confidence: 99%
“…P. intermedia, P. nigrescens, P. pallens, P. oris) are among the most dominant and prevalent bacteria isolated from dental abscesses and their severe complications due to bacterial spreading [11,12], as: brain [13,14], liver [15] or lung abscesses [16], mediastinitis [17], necrotizing fasciitis [17,l8], Ludwig's angina [19] and sepsis [20]. In facial cellulitis of dental origin, Prevotella was reported as the most frequently isolated anaerobic bacteria [21].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the quality of dental prescriptions is suggested to reduce the risks for medication errors and to promote the rational use of pharmacotherapy, and patient safety. In a population‐based study, tooth extraction was shown to be associated with a low but significant risk of postoperative sepsis, especially in the elderly and patients with underlying diseases. Further, owing to the danger of trans‐infection of blood‐borne diseases, dental practitioners are recommended to assess the risks of cross‐infection after dental extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Such reporting and analysis of errors can significantly help in the identification of the main contributing factors. According to all these studies, understanding the factors that lead to errors is essential for the consideration of changes that will prevent errors. It also needs to be considered that single events or errors most often result from the convergence of multiple contributing factors and preventing errors apparently requires a systems approach in order to modify the conditions that contribute to these errors.…”
Section: Introductionmentioning
confidence: 99%